2004
DOI: 10.1007/s10286-004-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the active standing test and head-up tilt test for diagnosis of syncope in childhood and adolescence

Abstract: We examined 51 children and adolescents with orthostatic symptoms using two orthostatic tests, the active standing test (the AS test) and head-up tilt test (HUT), and compared circulatory responses, autonomic function in addition to the induction rate of syncope during short-time orthostasis. Syncope was induced in eight patients with both tests, in only six patients with the AS test and in only one patient with HUT. The induction rate was significantly higher with the AS test (p<0.0001). In addition, the AS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
0
25
0
3
Order By: Relevance
“…Changes from supine to sitting to standing postures led to a shortening of interbeat interval and a decrease in RSA, reflecting the expected decrease in cardiac vagal activity that has been well documented in studies using either passive head-up tilting or active standing (Cooke et al, 1999;Furlan et al, 2000;Matsushima, Tanaka, & Tamai, 2004;Mukai & Hayano, 1995;Siebert, Drabik, Lango, & Szyndler, 2004).…”
Section: Discussionmentioning
confidence: 61%
“…Changes from supine to sitting to standing postures led to a shortening of interbeat interval and a decrease in RSA, reflecting the expected decrease in cardiac vagal activity that has been well documented in studies using either passive head-up tilting or active standing (Cooke et al, 1999;Furlan et al, 2000;Matsushima, Tanaka, & Tamai, 2004;Mukai & Hayano, 1995;Siebert, Drabik, Lango, & Szyndler, 2004).…”
Section: Discussionmentioning
confidence: 61%
“…A recent report examining the diagnostic discrimination of tilt-table testing and active standing in patients with neurally mediated syncope drew a similar conclusion in a younger population group. 11 The symptomatic and asymptomatic patients in the present study demonstrated no difference in severity or time of BP falls on tilt test. The relationship between symptoms and the magnitude of the BP fall in patients with orthostatic intolerance is not linear; some patients with autonomic failure with profound BP falls immediately after standing due to autonomic failure are asymptomatic while patients with postural tachycardia syndrome and minimal BP falls report severe symptoms of orthostatic intolerance.…”
Section: Resultsmentioning
confidence: 88%
“…This is possible, since brief static contractions in the leg muscles during upright stance will trigger the exercise and baroreceptor reflexes (Borst et al, 1982), thus resulting in an immediate increase in heart rate and thereby affecting blood flow. Furthermore, quiet standing was found to have a greater tendency to induce syncope when compared to HUT (Matsushima et al, 2004), which suggests that autonomic function and cardiovascular response differ between tilt and standing situations. Compared to isometric FES, passive mobilization and dynamic FES were able to either maintain or increase the mean IVC CSA , suggesting that these modalities are more effective for maintaining or improving circulatory hemodynamics under orthostatic conditions.…”
Section: Blood Flow Responsementioning
confidence: 88%